2016
DOI: 10.1182/blood-2015-07-658203
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase HERC4 mediates c-Maf ubiquitination and delays the growth of multiple myeloma xenografts in nude mice

Abstract: Key Points• HERC4 is the first identified ubiquitin ligase that mediates c-Maf ubiquitination and degradation.• HERC4 suppresses MM cell proliferation and delays MM tumor growth.The transcription factor c-Maf is extensively involved in the pathophysiology of multiple myeloma (MM), a fatal malignancy of plasma cells. In the present study, affinity chromatography and mass spectrometry were used to identify c-Maf ubiquitination-associated proteins, from which the E3 ligase HERC4 was found to interact with c-Maf a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 28 publications
(41 reference statements)
3
90
1
Order By: Relevance
“…Multiple myeloma (MM) is an incurable hematological malignancy derived from plasma cells, and it is the second highest blood cancer and accounts for 2% overall cancer cases. MM is featured with chromosomal translocations which lead to overexpression of several key genes, including the transcription factor c-Maf (13,14) which promotes MM cell proliferation and development (15,16). In the present study, we found that TMEPAI induces the ubiquitination and degradation of c-Maf and induces MM cell apoptosis independent of TGF-β signaling.…”
supporting
confidence: 48%
See 3 more Smart Citations
“…Multiple myeloma (MM) is an incurable hematological malignancy derived from plasma cells, and it is the second highest blood cancer and accounts for 2% overall cancer cases. MM is featured with chromosomal translocations which lead to overexpression of several key genes, including the transcription factor c-Maf (13,14) which promotes MM cell proliferation and development (15,16). In the present study, we found that TMEPAI induces the ubiquitination and degradation of c-Maf and induces MM cell apoptosis independent of TGF-β signaling.…”
supporting
confidence: 48%
“…Our previous studies have showed that ubiquitin ligase HERC4 and ubiquitin-conjugating enzyme UBE2O lead to c-Maf degradation (13,18). To find out whether there were any other enzymes that might mediate c-Maf degradation, a small collection of plasmids (The Hopsital for Sick Children, Toronto, Canada) that were involved in proteolysis was screened.…”
Section: Tmepai Induces C-maf Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have shown that HERC4 contributes to the occurrence and development of cancer. HERC4 plays an important role in myeloma (Zhang et al, 2016). In addition, some investigators verified that HERC4 highly expresses in lung cancer and breast cancer (Zhou et al, 2013;Zeng et al, 2015).…”
Section: Introductionmentioning
confidence: 98%